Analisis Biaya Volume Laba dan Biaya Diferensial Dalam Perencanaan Laba - Siti Nur Reskiyawati Said (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Cost-Volume-Profit (CVP) analysis is a managerial accounting tool used to examine the relationship between costs, sales volume, and company profitability. This study aims to analyze the role of CVP analysis and differential cost analysis in supporting profit planning and managerial decision-making in a culinary small and medium-sized enterprise (SME), anonymized as UMKM X. The research employs a descriptive quantitative method with a case study approach. Data were obtained from production costs, non-production costs, sales volume, and revenues generated from both regular and special orders. The results indicate that a special order of 900 portions sold at IDR 14,000 per portion generated a profit of IDR 3,070,000, which was higher than the profit from regular orders amounting to IDR 2,239,000. Although the selling price of the special order was lower, it yielded greater profit because it did not incur additional non-production costs. These findings demonstrate that differential cost analysis assists management in identifying more profitable decision alternatives. Furthermore, CVP analysis plays a significant role in profit planning by measuring the relationship between costs, sales volume, and profitability levels, thereby supporting more effective budgeting and managerial decision-making.